LC-MS/MS Method for Mycotoxin Analysis - Aldo Laganà (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Mycotoxins are secondary metabolites produced by some species of filamentous fungi belonging to Fusarium, Aspergillus, Penicillium, Claviceps and Alternaria genera. The biochemical significance of mycotoxins in fungal metabolism has not always been fully clarified; however, the main concern for mycotoxins is driven by the deleterious effects they can exert on human and animal health. Structurally, the mycotoxins currently known belong to heterogeneous chemical classes, therefore the toxic effects they can induce are highly diverse (e.g., cancerogenic and immunosuppressive effects). The main route of human exposure to mycotoxins is by intake of contaminated food, either directly from contaminated agricultural products, or indirectly from residues and metabolites present in foods of animal origin. Immunochemical methods are generally used for the fast screening of mycotoxin presence; however, for confirmation purposes, analytical methods based on high-performance liquid chromatography (LC) are preferred, especially when coupled with tandem mass spectrometry (MS/MS), which allows the determination of multiclass mycotoxins in a single analysis. Moreover, the technical innovations available in LC-MS/MS instrumentation are prompting its application to the monitoring of contaminants in food and feed. The aim of this paper collection, constituted by ten research articles and one review, is to provide the reader with an overview on the novelties and capabilities in LC-MS/MS-based multi-mycotoxin methods, also including the investigation of emerging and modified mycotoxins.
English
Keywords: Analytical methods; Mycotoxin extraction from cereals; Mycotoxins; Cereal contamination; LC-MS/MS: Multi-mycotoxin analysis